How Does Energy Efficiency Mitigate Carbon Emissions Without Reducing Economic Growth in Post COVID-19 Era - Li, Min; Yao-Ping Peng, Michael; Nazar, Raima; Ngozi Adeleye, Bosede; Shang, Meng; Waqas, Muhammad (Frontiers in Energy Research, 2022)
A comprehensive analytical study to assess the performance level of industrial functions in the environment has become necessary at the present time. According to existing research, the COVID-19 pandemic resulted in a significant reduction in carbon emissions in 2020. Policymakers are focusing on the discrepancies and negative environmental effect caused by various industries during their routine operations. This study aims to estimate the performance level of energy in the context of the environment of the countries that are members of the European Union This evaluation is performed through a data envelopment analysis (DEA) model, through which we have applied a non-proportional adjustment, taking into account the input of energy and its undesirable output. The DEA model allows dynamic assessment of sources in the field of measuring energy efficiency and its environmental effects. The score of measurement of efficiency lies between zero and one, which means China and Russia are awarded this score of one (1), which shows the highest level of efficiency in clean energy, while Bangladesh (0.19), Uzbekistan (0.09), Mongolia and Cambodia (0.06), and Kyrgyzstan (0.04) are at the lowest level of performance in clean energy. The results of the study showed that clean energy efficiency levels increased in all countries over the study period. The emission level of greenhouse gases in the first world countries was found to be better in the context of improvement in performance enhancement in the sector of the energy mix. Evasion score is measured as 365 kt of CO2. This score for NO2 is 280 kt and for SO2 is 82 kt, whereas it is 23 kt (0.24 kg/cap) of particulate hazardous matter. The higher performance level of energy yields a negative relationship with emissions of gases, with a significant number of 12% for NO2 in 2000, as compared to 13% for SO2 and 14% for PM2.5. Whereas PM10 has the highest concentration (18%). Public policymakers may enhance the facilitation system for better free trade and a result-oriented corporate environment to enhance the performance level of energy in the electric sector.